Pre-stretching of the Hamstrings Before Squatting Acutely Increases Biceps Femoris Thickness Without Impairing Exercise Performance - Trindade, Thiago Barbosa; Neto, Leônidas Oliveira; Pita, José Claudino Neto; Tavares, Vagner Deuel de Oliveira; Dantas, Paulo Moreira Silva; Schoenfeld, Brad J.; Prestes, Jonato (Frontiers in Physiology, 2020)
Background: Bilateral squat exercise is widely used in resistance training programs to increase lower limb strength and muscle mass, but this exercise does not result in significant hypertrophy of the hamstrings. It has been speculated that stretching between sets with a certain degree of tension results in muscle hypertrophy, while acute stretching could decrease performance during maximal contractions. Objective: This study investigated the acute effects of hamstring stretching before bilateral squatting on muscle thickness (MT), electromyography (EMG), and total training volume on exercise performance. Methods: Fourteen resistance-trained young men, with ~7.5 years of RT experience, performed the 10 repetition maximum (RM) for the barbell squat in 2 sessions (test-retest) separated by period after 48h. Participants engaged in two resistance exercise conditions separated by a one week recovery interval: one session employed hamstrings stretching and the other did not include hamstrings stretching. Before and after each resistance exercise session, the thickness of the quadriceps muscles and biceps femoris long head were obtained by ultrasound imaging. Moreover, the EMG amplitudes for the quadriceps muscles, biceps femoris, and iliocostalis muscles were recorded during back squat performance. The total training volume was also evaluated for each exercise session. Results: A significant increase in MT was observed after every set in both conditions for the evaluated quadriceps muscles (all p< .05), while for the biceps femoris this effect was found only in the stretching condition (p<.05). EMG activity increased in the rectus femoris, vastus lateralis, and vastus medialis for the stretching condition. For the non-stretching condition, activity only increased in the vastus lateralis and medialis. There was no difference in EMG activity for the biceps femoris and iliocostalis in both conditions. Conclusion: Stretching the hamstrings immediately before each set of the back squat can be used to acutely increase biceps femoris thickness without impairing squat performance.